A City Profile of Malaga: The Role of the Port-City Border throughout Historical Transformations - Andrade, María J. (2021)
The relationships Malaga has established with its port have changed over the centuries, conjuring up a variety of scenarios and circumstances. The past and present are closely linked phenomena in this case study where the porosity of the port‐city fabric has marked the city’s development and constitutes a key issue in the current and future challenges it faces. Malaga provides a particularly interesting example of a post‐industrial city that has reopened its port to its inhabitants’ acclaim while maintaining port activity. However, the growth tourism has seen in recent years has come to dominate the local economy. Cruise ships have taken on a significant role and have brought about important changes in the dynamics and flows between the port and the city, unsettling the balance between the two. This profile explores port‐city development through the lens of boundaries and flows, demonstrating how their dynamics have determined Malaga’s spatial, functional, and social development over time and how they continue to do so to this day. This article reviews the transformations the city has undergone and its future opportunities to achieve a balanced and sustainable port‐city relationship.